Ahli Waris Pengganti dalam Penerapan Pasal 185 Kompilasi Hukum Islam : Studi Analisis Terhadap Putusan Pengadilan Agama Jember Nomor: 1378/Pdt.G/2019/PA. Jember - Alfina Wildatul Fitriyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
Compilation of Islamic Law is a set of rules of Islamic Law that contains descriptions or certain law materials, Law opinions or legal rules. The heirs in the Compilation of Islamic Law are classified into three groups, namely Dzawi al-furudl al-muqad, ' Ashabah, and surrogate heir. The surrogate heir is the person who gets the inheritance to replace the real heir because he died earlier than the heir. In this study the author wants to describe clearly and in detail about The Surrogate Heirs in the Application of article 185 of the Complication of Islamic Law (Analytical Study of the Decisions of the Jember Religious Court Number: 1378/Pdt.G/2019/PA. Jember). The study used qualitative research methods. From the results of the study, the authors have two conclusions, namely: First The Surrogate Heirs in the Application of article 185 of the Complication of Islamic Law The concept of surrogate heir is not only on the upward and downward path, but can also be carried out on the sideways path and the share of the surrogate heir should not exceed from the share of the heirs who are equal to and replaced. Second, the decision of the Jember Religious Court judge number /Pdt.G/2019/PA.Jember gives a share to sons and daughters of sisters (nieces) on the grounds that they are surrogate heir can be justified based on the views of the Jember Religious Court judges. and Islamic law. Because the surrogate heir are relevant to the lafadz al-mawaali in the snippet of verse 33 of Surah An-Nisa’